Adrenal crisis during pregnancy: Case report and obstetric perspective - Gardella, Barbara; Gritti, Andrea; Scatigno, Annachiara Licia; Gallotti, Anna Maria Clelia; Perotti, Francesca; Dominoni, Mattia (Frontiers in Medicine, 2022)
Adrenal dysfunction and in particular adrenal crisis are uncommon events in pregnant women, but associated with significant maternal and fetal morbidity and mortality if untreated or undiagnosed. Adrenal crisis may be confused with the common symptoms of pregnancy: the obstetricians should be able to promptly diagnose and treat it in order to avoid the adverse outcomes regarding the mother and the fetus. For this reason adrenal dysfunction must be treated by an expert multidisciplinary team. We presented a case report of a young pregnant woman with adrenal crisis due to tuberculosis, cocaine abuse, and massive bilateral hemorrhage with symptoms of emesis, hypotension, sudden abdominal pain, and leucocytosis. The most common issues of diagnosis and treatment are discussed and analyzed. Finally, we performed a review of the literature regarding adrenal crisis and adrenal insufficiency in pregnancy in order to clarify the management of these diseases in obstetrics setting.